Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Cos(a)+ cos(b)+ cos(c)+ cos(a+b+c)=4cos([a+b]/2)cos([b+c]/2)cos([a+c]/2)

Cos(a)+ cos(b)+ cos(c)+ cos(a+b+c)=4cos([a+b]/2)cos([b+c]/2)cos([a+c]/2)

Grade:11

1 Answers

Sanskar sharma 814
42 Points
4 years ago
Proof=Let the RHS of given equation be EE= 2cos([a+b]/2)cos([a-b]/2)+2cos([a+b+2c]/2)cos([a-b]/2)=2cos([a+b]/2){2cos([a+c]/2)cos([b+c]/2)}=4cos([a+b]/2)cos([b+c]/2)cos([a+c]/2) LHS=RHS(use cos(m) +cos (n) = 2cos([m+n]/2)cos([m-n]/2)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free